Factor Affecting Adoption of E-Wallet in Sarawak - Lee, Kelvin Yong Ming; Mohamad, Jais; Chan, Chia Wen; Nurul Syuhada, Zaidi (HRMARS, 2020)
E-wallet was an innovative payment instrument that arises under financial technology. E-wallet helps to ease the user’s daily life, in which users can make their daily transactions without using the notes or coins. Indirectly, E-wallet also helps to reduce the risk of cash being stolen. Undeniably, E-wallet brings more benefits than disadvantages. The primary aim of this study is to examine the factors affecting the adoption of E-wallet services in Sarawak. The questionnaire, which consisted of 26 questions were distributed to the respondents and successfully collected 450 feedbacks. Firstly, this study applied factor analysis to construct all the variables. Also, Cronbach’s α coefficient was computed to determine internal consistency reliabilities. Then, this study used regression analysis to test the relationship between the variables. The results of the regression analysis showed that the users would adopt E-wallet when they perceive that the E-wallet is useful and easy to be used. Meanwhile, the findings of this study also showed that rewards tend to attract users to use E-wallet. Besides that, this study also found that higher perceived risk may act as a barrier to stop users from using E-wallet. These results help the E-wallet service providers to identify the significant factors that influence the user’s intention to use E-wallet services. Lastly, this study recommended the E-wallet service providers to take the security systems and rewards into consideration for the enhancement of their payment system.